The effect of sediment resuspension on pelagic nitrogen fixation in a Danish fjord - Sediment characteristics - Isabell Schlangen; Carolin Regina Löscher; Karl Michael Attard; Lisbeth Fürst Sørensen; Lasse Riemann (PANGAEA, 2025)
This dataset contains sediment characteristics relevant to assessing the potential impact of sediment resuspension on biogeochemical processes in a microtidal fjord system. Sediment samples were collected seasonally during June, July, August, and September 2023 from Kærby Fed in Odense Fjord, Denmark. The data provide baseline information on sediment composition and nutrient content under varying natural conditions. Measured parameters include: (i) concentrations of dissolved inorganic nitrogen (DIN) and dissolved inorganic phosphorus (DIP), analyzed using a spectrophotometer, (ii) particulate organic carbon (POC) and particulate organic nitrogen (PON), determined by Elemental Analysis–Isotope Ratio Mass Spectrometry, (iii) sediment chlorophyll a (Chl a), measured using a fluorometer, (iv) physical sediment properties, including density, water content, and porosity. Samples were processed in triplicates, and the dataset includes standard deviations to account for measurement variability. These data serve as a geochemical context for related studies investigating sediment resuspension and nutrient cycling in the Danish Baltic Sea region.